Key terms for the assessment of the safety of vaccines in pregnancy: Results of a global consultative process to initiate harmonization of adverse event definitions - Munoz, Flor M. (Vaccine, 2015)
BACKGROUND: The variability of terms and definitions of Adverse Events Following Immunization (AEFI) represents a missed opportunity for optimal monitoring of safety of immunization in pregnancy. In 2014, the Brighton Collaboration Foundation and the World Health Organization (WHO) collaborated to address this gap. METHODS: Two Brighton Collaboration interdisciplinary taskforces were formed. A landscape analysis included: (1) a systematic literature review of adverse event definitions used in vaccine studies during pregnancy; (2) a worldwide stakeholder survey of available terms and definitions; (3) and a series of taskforce meetings. Based on available evidence, taskforces proposed key terms and concept definitions to be refined, prioritized, and endorsed by a global expert consultation convened by WHO in Geneva, Switzerland in July 2014. RESULTS: Using pre-specified criteria, 45 maternal and 62 fetal/neonatal events were prioritized, and key terms and concept definitions were endorsed. In addition recommendations to further improve safety monitoring of immunization in pregnancy programs were specified. This includes elaboration of disease concepts into standardized case definitions with sufficient applicability and positive predictive value to be of use for monitoring the safety of immunization in pregnancy globally, as well as the development of guidance, tools, and datasets in support of a globally concerted approach. CONCLUSIONS: There is a need to improve the safety monitoring of immunization in pregnancy programs. A consensus list of terms and concept definitions of key events for monitoring immunization in pregnancy is available. Immediate actions to further strengthen monitoring of immunization in pregnancy programs are identified and recommended.